FAMILY SUPPORT IN IMPROVING INDEPENDENCE OF STROKE PATIENTS - Setyoadi Setyoadi; Tina Handayani Nasution; Amanda Kardinasari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Stroke is a condition which occurs when the brain's blood vessels fail to supply oxygen to the brain cells which caused the brain not functioning properly. As such, stroke patients cannot fully support themselves. However, with constant and proper treatment, it can ease the burden on the patients, minimizing their disability, and reducing their dependence towards others while undergoing an activity. During the recovery phase, family plays an important role, they served as a source of support even during the healing and rehabilitation phase, as such, they are expected to be involved in the process of treatment since the very beginning. The purpose of this study is to identify the correlation of family support with stroke patients’ independence in the medical rehabilitation center of Dr. Iskak hospital Tulungagung. In order to focus on the stroke patients, this research uses a purposive sampling method which follows certain predetermined criteria. The research data were collected by using structured interview techniques by utilizing Barthel Index’s Instrument and family support instrument. Based on the results of the study, out of 57 respondents, the average score for family support was 87,84 while the stroke patients’ independence receives an average score of 81,75. Statistical analysis showed significant value = 0.00 whereas its sig value <α = 0.05 These numbers show a strong connection between family support with independence, which means that there is a correlation between family support and stroke patients independence. In conclusion, by giving a better family support the stroke patients can gradually become more independent. Essentially, in order for the stroke patients to gain better condition, it is advised that the paramedics should improve their role in providing education about the importance of family support towards stroke patients’ family members as the family plays an important role during the recovery process.